Effect of arthroscopic repair on sleep disturbances in rotator cuff tear patients: A prospective cohort study analyzing short-term postoperative pain correlations - Hyojune Kim; Jangwon Lee; Kyoung Hwan Koh (Journal of Orthopaedic Surgery, 2025)
Purpose The aim is to explore the impact of rotator cuff repair on sleep quality and its correlation with postoperative pain and recovery. Methods A prospective cohort study from December 2022 to May 2023 was conducted on 28 patients undergoing arthroscopic rotator cuff repair. Pre- and postoperative sleep quality was assessed using the Korean version of the Pittsburgh Sleep Quality Index (K-PSQI), and pain was measured using the pain visual analog scale (pVAS). Sleep duration was monitored using Fitbit Inspire 2 trackers post-surgery. Statistical analyses were conducted to evaluate the relationship between sleep quality, pain, and postoperative recovery. Results The mean preoperative PSQI score (9.5 ± 6.0) indicated sleep disturbances, with elevations in sleep latency and disturbances. Six weeks post-surgery, PSQI decreased significantly to 6.4 ± 3.3 ( p = .03), with marked improvements in sleep quality and efficiency. Mean pVAS scores consistently declined post-operation, while sleep duration increased. A statistically significant correlation ( p < .05) existed between pVAS score reduction and sleep duration increment. Additionally, preoperative PSQI scores significantly correlated with ‘Daily pVAS decrease’ and ‘Daily sleep duration increase’. Conclusions We demonstrate that rotator cuff repair leads to improvements in sleep quality and reductions in pain. However, the persistently high postoperative PSQI scores suggest that sleep disturbances may not be entirely resolved by surgery alone. These findings highlight the need for comprehensive perioperative care in rotator cuff tear patients, incorporating both surgical and non-surgical strategies to manage sleep disturbances and enhance overall patient outcomes. Level of evidence Level III, Prospective cohort study.